1972
DOI: 10.4319/lo.1972.17.5.0763
|View full text |Cite
|
Sign up to set email alerts
|

Coprecipitation of Phosphate With Carbonates in a Marl Lake

Abstract: High concentrations of phosphate ion precipitate with carbonates by simple coprecipitation as the pH of marl lake water is increased. High pH microenvironments associated with photosynthesis probably induce phosphate‐carbonate precipitation, which in turn functions as one of several indirect density‐dependent population controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
1
4

Year Published

1980
1980
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(111 citation statements)
references
References 6 publications
5
101
1
4
Order By: Relevance
“…Geochemical modeling using Visual Minteq 3.1 indicated that at pH b 8.0, the aqueous solutions in our suspensions were oversaturated with respect to Ca-phosphates, and also became oversaturated with respect to calcite as pH approached 9.0. Phosphate may co-precipitate with particulate carbonates, which promotes P i accumulation (Otsuki and Wetzel, 1972). Calcite was detected by XRD in our original periphyton stock suspensions (Fig.…”
Section: Effect Of Ca(ii) On P I Accumulationmentioning
confidence: 89%
“…Geochemical modeling using Visual Minteq 3.1 indicated that at pH b 8.0, the aqueous solutions in our suspensions were oversaturated with respect to Ca-phosphates, and also became oversaturated with respect to calcite as pH approached 9.0. Phosphate may co-precipitate with particulate carbonates, which promotes P i accumulation (Otsuki and Wetzel, 1972). Calcite was detected by XRD in our original periphyton stock suspensions (Fig.…”
Section: Effect Of Ca(ii) On P I Accumulationmentioning
confidence: 89%
“…Moreover, the possibility for charophytes to use bicarbonate as a carbon source for photosynthesis leads to the formation of carbonate, which in turn can precipitate with calcium to form calcite (Otsuki & Wetzel, 1972). Calcite can subsequently co-precipitate with phosphate, which is a redox-insensitive reaction (Otsuki & Wetzel, 1972). Charophytes can thus enhance the binding capacity of iron.…”
Section: Iron As a Measure To Control Eutrophicationmentioning
confidence: 99%
“…Charophytes are able to oxidize the sediment, thereby preventing this redoxreaction to occur (Kufel & Kufel, 2002). Moreover, the possibility for charophytes to use bicarbonate as a carbon source for photosynthesis leads to the formation of carbonate, which in turn can precipitate with calcium to form calcite (Otsuki & Wetzel, 1972). Calcite can subsequently co-precipitate with phosphate, which is a redox-insensitive reaction (Otsuki & Wetzel, 1972).…”
Section: Iron As a Measure To Control Eutrophicationmentioning
confidence: 99%
“…These, together with calcium ions form insoluble calcite which precipitates in a form of tiny settling particles (the so-called lake "whiting") or as an incrustation covering some macrophytes (mainly charophytes). Phosphorus may adsorb on and coprecipitate with calcite particles [MURPHYet al 1983;OTSUKI, WETZEL 1972] or even convert calcite into hydroxyapatite [STUMM, MORGAN 1970]. In general, combination of mineral P with calcite is non-stoichiometric and it is impossible to calculate the amount of immobilised P from phosphate and calcium concentrations.…”
Section: Some Notes On Nutrient Cycling In Fishpondsmentioning
confidence: 99%